PENGARUH LABEL HALAL DAN CITRA MEREK TERHADAP MINAT BELI PRODUK KECANTIKAN (STUDI LITERATUR REVIEW MANAJEMEN PEMASARAN) - Dillahi, Hikma; Hidayat, Rahmadani; nirwana, Nina; Ningsih, Rinda Ayu (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2025)
This literature article discusses halal labels and brand image, the purpose of this study is to determine the variables of Brand Image and Halal Labeling that influence Purchase Intention. The writing method is a literature review which is a library research method that comes from online media such as Google Scholar, Mendelay, and other online media. Previous and related research helps support theories and phenomena regarding the relationship and effects between variables. The results of this literature study are as follows: 1). Brand Image influences Purchase Intention 2) Halal Labeling influences Purchase Intention Keywords: Halal Label, Brand Image and Purchase Interest